Hubungan Antara Moral Judgment Maturity Dan Perilaku Cheating Pada Siswa Mas Bahrul Ulum Pulau Tello, Nias Selatan - Nahdah Melayu, Rudhahtul; Candra, Ifani; Anggawira, Andhika (Holistic Science, 2022)
This study aims to determine the relationship between Moral Judgment Maturity and Cheating Behavior in MAS Bahrul Ulum Students, Tello Island, South Nias. The independent variable in this study is Moral Judgment Maturity and the dependent variable is Cheating Behavior. The measuring instrument used in this research is the Likert scale and the Cheating Behavior scale. The sampling technique in this study used a random sampling technique. The sample in this study was 105 students at MAS Bahrul Ulum Tello Island, South Nias. Test the validity and reliability in this study using the Alpha Cronbach technique. The results of the validity coefficient on the Moral Judgment Maturity scale move from rix = 0.377 to rix = 0.701 with a reliability coefficient of = 0.878 while the Cheating Behavior scale moves from rix = 0.355 to rix = 0.760 with a reliability coefficient of = 0.927. Based on data analysis, obtained a correlation value of -0.425 with a significance level of 0.000, which means the hypothesis is accepted. This shows that there is a significant relationship between Moral Judgment Maturity and Cheating Behavior in MAS Bahrul Ulum Students, Tello Island, South Nias, in a negative direction. The results of the analysis of the effective contribution of Moral Judgment Maturity with Cheating Behavior is 18% while 82% is influenced by other factors